Cytomegalovirus vector expressing RAE‐1γ induces enhanced anti‐tumor capacity of murine CD8+ T cells. Issue 8 (4th July 2017) - Tršan, Tihana; Vuković, Kristina; Filipović, Petra; Brizić, Ana Lesac; Lemmermann, Niels A. W.; Schober, Kilian; Busch, Dirk H.; Britt, William J.; Messerle, Martin; Krmpotić, Astrid; Jonjić, Stipan
Abstract : RAE‐1γMCMV vector promotes induction of epitope specific KLRG1‐expressing CD8 T cells with enhanced effector functions providing superior protection against tumor challenge. Abstract : Designing CD8 + T‐cell vaccines, which would provide protection against tumors is still considered a great challenge in immunotherapy. Here we show the robust potential of cytomegalovirus (CMV) vector expressing the NKG2D ligand RAE‐1γ as CD8 + T cell‐based vaccine against malignant tumors. Immunization with the CMV vector expressing RAE‐1γ, delayed tumor growth or even provided complete protection against tumor challenge in both prophylactic and therapeutic settings. Moreover, a potent tumor control in mice vaccinated with this vector can be further enhanced by blocking the immune checkpoints TIGIT and PD‐1. CMV vector expressing RAE‐1γ potentiated expansion of KLRG1 + CD8 + T cells with enhanced effector properties. This vaccination was even more efficient in neonatal mice, resulting in the expansion and long‐term maintenance of epitope‐specific CD8 + T cells conferring robust resistance against tumor challenge. Our data show that immunomodulation of CD8 + T‐cell responses promoted by herpesvirus expressing a ligand for NKG2D receptor can provide a powerful platform for the prevention and treatment of CD8 + T‐cell sensitive tumors.